Correlation between waist circumference and glycated haemoglobin (HbA1c) among type 2 diabetes mellitus patients in Diabetic Polyclinic Sanglah General Hospital - Wan Muhamad Syafiq; I Made Pande Dwipayana; Made Ratna Saraswati; Wira Gotera (Indoscholar, 2020)
Background: Diabetes mellitus (DM) is an interminable issue that can modify glucose, protein, and fat digestion caused by the absence of insulin discharge due to either the dynamic or checked powerlessness of the β-Langerhans islet cells of the pancreas to create insulin. The prevalence of type 2 diabetes mellitus parallels the expanding prevalence of obesity and central obesity. The prevalence of obesity and central obesity in Indonesian among the adult populations are 23.1% and 28%, respectively. Obesity and central obesity are associated with a higher risk of DM. The accumulation of adipose tissue in certain parts of the body, such as in the abdominal cavity, causes an increased risk of insulin resistance until the onset of the metabolic syndrome. This study aims to determine the correlation between waist circumference and glycated haemoglobin (HbA1c) among type 2 DM patients in Diabetic Polyclinic Sanglah General Hospital. Methods: This study was an observational analytic study using a cross-sectional method. Samples selected using consecutive sampling, which determined based on inclusion and exclusion criteria from the population. The total of study subject was 70 respondents. Result: The results of the study showed a significant relationship between waist circumference and HbA1c among type 2 diabetes mellitus patients (p = 0.012) with a low correlation (r = 0.300). Conclusion: Conclusion of this study that there is a relationship between waist circumference and HbA1c among type 2 diabetes mellitus patients in Diabetic Polyclinic Sanglah General Hospital.